2010
DOI: 10.1371/journal.pone.0014211
|View full text |Cite
|
Sign up to set email alerts
|

Desmoglein 3, via an Interaction with E-cadherin, Is Associated with Activation of Src

Abstract: BackgroundDesmoglein 3 (Dsg3), a desmosomal adhesion protein, is expressed in basal and immediate suprabasal layers of skin and across the entire stratified squamous epithelium of oral mucosa. However, increasing evidence suggests that the role of Dsg3 may involve more than just cell-cell adhesion.Methodology/Principal FindingsTo determine possible additional roles of Dsg3 during epithelial cell adhesion we used overexpression of full-length human Dsg3 cDNA, and RNAi-mediated knockdown of this molecule in vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
105
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(123 citation statements)
references
References 60 publications
18
105
0
Order By: Relevance
“…Emerging evidence suggests a cross talk between Dsg3 and E-cadherin showing that Dsg3 regulates E-cadherin adhesion via signal pathways such as Src, Rho GTPases Rac1/cdc42 and Ezrin as well as transcription factor cJun/AP-1, all of which are involved in the organization of actin cytoskeleton associated with adherens junctions. [7][8][9][10] This novel finding has recently been reported by independent studies in the literature that demonstrate existence of a complex formation containing non-junctional Dsg3, E-cadherin and Src in keratinocytes. [7][8][9][10] Furthermore, it has been suggested that the stability of such a complex is Src dependent and the tyrosine phosphorylation of cadherins is required for recruiting Dsg3 to the cytoskeletal pool and for desmosome maturation.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Emerging evidence suggests a cross talk between Dsg3 and E-cadherin showing that Dsg3 regulates E-cadherin adhesion via signal pathways such as Src, Rho GTPases Rac1/cdc42 and Ezrin as well as transcription factor cJun/AP-1, all of which are involved in the organization of actin cytoskeleton associated with adherens junctions. [7][8][9][10] This novel finding has recently been reported by independent studies in the literature that demonstrate existence of a complex formation containing non-junctional Dsg3, E-cadherin and Src in keratinocytes. [7][8][9][10] Furthermore, it has been suggested that the stability of such a complex is Src dependent and the tyrosine phosphorylation of cadherins is required for recruiting Dsg3 to the cytoskeletal pool and for desmosome maturation.…”
Section: Introductionsupporting
confidence: 74%
“…[7][8][9][10] This novel finding has recently been reported by independent studies in the literature that demonstrate existence of a complex formation containing non-junctional Dsg3, E-cadherin and Src in keratinocytes. [7][8][9][10] Furthermore, it has been suggested that the stability of such a complex is Src dependent and the tyrosine phosphorylation of cadherins is required for recruiting Dsg3 to the cytoskeletal pool and for desmosome maturation. 7 Moreover, it has been shown that overexpression of Dsg3 in cancer cell lines does not necessarily enhance cell-cell adhesion but rather causes a reduction of E-cadherin expression with concomitant accelerated cell migration and invasion.…”
Section: Introductionsupporting
confidence: 74%
“…Accordingly, direct RhoA inhibition leads to pemphigus skin blistering (Waschke et al 2006). In addition to its negative effects on desmosome function, Dsg3 internalization also promotes loss of E-cadherin through Src, possibly thereby having a more general effect on cellcell adhesion (Tsang et al 2010(Tsang et al , 2012b. However, others report that siRNA-mediated silencing of Dsg1 and/or Dsg3 does not significantly affect the observed IgG-dependent increase in Src and EGFR signaling, suggesting that other targets may be involved in activating these tyrosine kinases (Grando 2012).…”
Section: Desmosomes In Epidermal Autoimmune Disorders and Under Attacmentioning
confidence: 99%
“…In turn, desmosome molecules regulate contractile signaling through Pkp2, which recruits active RhoA at cell -cell interfaces to drive actin reorganization and actin-dependent desmosome assembly . Dsg3 also dictates cytoskeletal organization and cell migration through regulation of the Rho GTPases Rac-1 and Cdc42 (Tsang et al 2010(Tsang et al , 2012a. Finally, desmosomes help remodel the microtubule cytoskeleton during epidermal stratification.…”
Section: Regulation Of Desmosome Dynamics Remodeling and Turnovermentioning
confidence: 99%
“…Interestingly, this phenotype may be observed in some kind of cancers (e.g. SCC) [171]. Moreover, it is estimated that 35% of cancers show increased MAPK activity [172].…”
Section: Malignancy In Relation To the Autoimmunity In Pemphigus Groumentioning
confidence: 98%